Calcium and IP3 dynamics in cardiac myocytes: experimental and computational perspectives and approaches - Hohendanner, Felix; McCulloch, Andrew D.; Blatter, Lothar A.; Michailova, Anushka P. (Frontiers in Pharmacology, 2014)
Calcium plays a crucial role in excitation-contraction coupling (ECC), but it is also a pivotal second messenger activating Ca2+-dependent transcription factors in a process termed excitation-transcription coupling (ETC). Evidence accumulated over the past decade indicates a pivotal role of inositol 1,4,5-trisphosphate receptor (IP3R)-mediated Ca2+ release in the regulation of cytosolic and nuclear Ca2+ signals. IP3 is generated by stimulation of plasma membrane receptors that couple to phospholipase C (PLC), liberating IP3 from phosphatidylinositol 4,5-bisphosphate (PIP2). An intriguing aspect of IP3 signaling is the presence of the entire PIP2-PLC-IP3 signaling cascade as well as the presence of IP3Rs at the inner and outer membranes of the nuclear envelope (NE) which functions as a Ca2+ store. The observation that the nucleus is surrounded by its own putative Ca2+ store raises the possibility that nuclear IP3-dependent Ca2+ release plays a critical role in ETC. This provides a potential mechanism of regulation that acts locally and autonomously from the global cytosolic Ca2+ signal underlying ECC. Moreover, there is evidence that: (i) the sarcoplasmic reticulum (SR) and NE are a single contiguous Ca2+ store; (ii) the nuclear pore complex is the major gateway for Ca2+ and macromolecules to pass between the cytosol and the nucleoplasm; (iii) the inner membrane of the NE hosts key Ca2+ handling proteins including the Na+/Ca2+ exchanger (NCX)/GM1 complex, ryanodine receptors (RyRs), nicotinic acid adenine dinucleotide phosphate receptors (NAADPRs), Na+/K+ ATPase and Na+/H+ exchanger. Thus, it appears that the nucleus represents a Ca2+ signaling domain equipped with its own ion channels and transporters that allow for complex local Ca2+ signals. Many experimental and modeling approaches have been used for the study of intracellular Ca2+ signaling but the key to understanding of the dual role of Ca2+ mediating ECC and ECT lays in quantitative differences of local [Ca2+